Four-armed figure of a seated Lakshmi - Temples of India Project Team (Jio Institute, 2024)
A four-armed figure of a seated Lakshmi with lotuses in her upper two hands, while her lower left hand holds a pot and the lower right is in the varada mudra. She is referred to as Goddess Leeliya on the museum label. She is accompanied by female attendants holding flowers on either side. The sculpture is housed in the Government Museum, Sikar.